EFEKTIFITAS MEANINGFUL LEARNING TERHADAP TANGGUNG JAWAB ANAK KELOMPOK B USIA 3-4 TAHUN DI PLAYGROUP AMANAH BUNDA MALANG - Nur Fitriana Dewi; Ayu Asmah; Siti Muntomimah (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2021)
Responsibility is part of the social emotional aspect that must be accustomed to early on with the aim of children being able to consistently be responsible both to themselves and to others, including being able to urinate independently, be patient waiting their turn and have a tolerant attitude so that they can work in groups. The previous habit is by inviting the child to be responsible when the teacher reminds and invites the child to be responsible and when the teacher does not remind the child is not responsible for their obligation. The next habituation is by giving children meaningful learning in which children will be given more meaningful learning and children not only doing activities but also understanding every activity carried out so that children’s responsibilities become better. This research was conducted using quantitative research with experimental methods and one group pre-test post-test design. Data collection techniques used observation, tests and documentation, then the data went through several tests, including validity, reliability, normality an hypothesis testing with the help of the SPSS.22 application.